E. THE PROPOSED 75 CENT AND $1.25 PER PACK CIGARETTE TAX HIKES COMPARED TO THE 1993 (930000) TAX CHANGES. (Tufts Archival Research Center, 2007)
Analysis of the impact of two proposed cigarette tax increases in 1994. Calculates average costs per smoker and for various income groups. Labels proposals as regressive. Presents tables and graphs comparing the effects to those of the 1993 tax increase.